Regulation of miR-1-Mediated Connexin 43 Expression and Cell Proliferation in Dental Epithelial Cells - Nakamura, Tomoaki; Iwamoto, Tsutomu; Nakamura, Hannah M.; Shindo, Yuki; Saito, Kan; Yamada, Aya; Yamada, Yoshihiko; Fukumoto, Satoshi; Nakamura, Takashi (Frontiers in Cell and Developmental Biology, 2020)
Many genes encoding growth factors, receptors, and transcription factors are induced by the epithelial-mesenchymal interaction during tooth development. Recently, the diverse functions of micro RNAs (miRNAs) have been reported in organogenesis and disease. miRNAs regulate gene expression by inhibiting translation and destabilizing mRNAs. However, the expression and function of miRNAs in tooth development remain poorly understood. We screened the expression of miRNAs produced during tooth development using a microarray system to clarify the role of miRNAs in dental development. micro RNA-1 (miR-1) showed a unique expression pattern in the developing tooth. Peak miR-1 expression in the tooth germ was detected at embryonic 16.5 days, with gradually decreasing expression at postnatal 1 and 3 days. According to an in-situ hybridization assay, miR-1 is expressed at the cervical loop of the dental epithelium. The expression of miR-1 and connexin 43, a target of miR-1, were inversely correlated both in vitro and in vivo. Knockdown of miR-1 induced the expression of Cx43 in dental epithelial cells. Interestingly, cells with reduced miR-1 expression proliferated slower than control cells. Immunocytochemistry revealed that Cx43 in miR-1 knockdown cells formed both cell-cell gap junctions and hemichannels at the plasma membrane. Furthermore, the rate of ATP release in miR-1 knockdown cells was higher than in control cells. In addition, downregulation of Cx43 expression in developing molars was observed in Epiprofin knockout mice, as well as the induction of miR-1 expression. These results suggest that the expression pattern of Cx43 is modulated by miR-1 to control cell proliferation activity during dental epithelial cell differentiation.